1993
DOI: 10.1366/0003702934334697
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Determination of Molecular Orientation and Surface Concentration in Anisotropic Monolayers on Liquid Substrates

Abstract: A new method is developed for the simultaneous determination of chain orientation and surface concentration in monolayers on liquid substrates. The method is based on the use of s- and p-polarized reflection-absorption (RA) infrared intensities in conjunction with an optical model that includes anisotropy in the optical constants. The advantages and limitations of the method are explored in detail. A modeling assessment of the RA p/RA s ratio leads to information on how the ratio can be used to qualitatively i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 19 publications
0
48
1
Order By: Relevance
“…A series of the MO measurements has been performed on the basis of approximation 10. 11,13,18,24,30,31,32,[49][50][51] However, the difference between 3k iso and k max can be essential. For example, the value of 3k iso ) 0.79 characterizes bulk CdAr dispersed in KBr pellets, 49 which is distinct from the value of k max ) 1.04 found for a 11-monolayer LB film of CdAr on glass.…”
Section: Methodsmentioning
confidence: 99%
“…A series of the MO measurements has been performed on the basis of approximation 10. 11,13,18,24,30,31,32,[49][50][51] However, the difference between 3k iso and k max can be essential. For example, the value of 3k iso ) 0.79 characterizes bulk CdAr dispersed in KBr pellets, 49 which is distinct from the value of k max ) 1.04 found for a 11-monolayer LB film of CdAr on glass.…”
Section: Methodsmentioning
confidence: 99%
“…The radiotracer technique is one of the earliest methods which can probe surface density directly (23)(24)(25). Recently, neutron reflection (26,27), second harmonic generation (28), ellipsometry (28)(29)(30)(31), and infrared reflection absorption spectroscopy (IRRAS) (18,21) have also been used for determining the surface density of soluble monolayers. Comparisons of the strengths and weaknesses of several of these techniques in determining surface coverage, molecular orientation, and hydrocarbon chain conformational state have been given in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative RA analysis was adopted to evaluate the molecule loss of the monolayers at the air/water interface. It has been reported that the RA intensity is in a linear relationship with the molecular surface density under the similar molecular orientation or conformation 39,46,47 . The relationship is reasonably described by 31 .…”
Section: Irras Analysismentioning
confidence: 99%